An experimental comparison of two preconditioned iterative methods to solve the elliptic partial differential equations - Seyyed Ahmad Edalatpanah (Computational Algorithms and Numerical Dimensions)
System of linear equations plays an important role in science and engineering. One of the applications of this system occurs in the discretization of the partial differential equations. This paper aims to investigate an experimental comparison between two kinds of iterative models for solving the elliptic partial differential equations. Different tools of solution such as stationary and non-stationary iterative methods with preconditioning models have been studied. Two types of discretization schemes (centered and hybrid) have been also considered for the comparison of the solution.